QUANTITATIVE EVALUATION OF BUFFALO SEMEN BY CASA DURING CRYOPRESERVATION PROCESS - KUMAR, DHARMENDRA; KUMAR2, PRADEEP; YADAV, P s (The Indian Journal of Animal Reproduction, 2016)
The present study evaluated the quantitative impact of cryopreservation on buffalo bull sperm with the use of computer assisted semen analyzer (CASA). The motility and kinetics parameters were not affected during equilibration (p>0.05), except curvilinear velocity (VCL), average lateral head displacement and viability, but total motility (83.07±0.57%), progressive motility (47.56±0.70%) and rapid motility (64.17±1.17%) of fresh semen reduced to 57.41±0.92%, 23.56±0.60% and 30.47±0.88%, respectively in frozen-thawed semen (p<0.05). Freezing and thawing procedures reduced average path velocity (27.5%), straight linear velocity (27%), VCL (21%), and beat cross frequency (11.5%) of sperm (p<0.05). In conclusion, motility and kinetics of buffalo sperm remained unaffected at equilibration stage, whereas, freeze-thawing process caused damage to motility apparatus and reduced total, progressive and rapid sperm motility.